2002
DOI: 10.1210/en.2002-220261
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone (GH) and GH-Releasing Peptide-6 Increase Brain Insulin-Like Growth Factor-I Expression and Activate Intracellular Signaling Pathways Involved in Neuroprotection

Abstract: Beneficial effects of GH on memory, mental alertness, and motivation have been documented. Many actions of GH are mediated through IGF-I; hence, we investigated whether systemic administration of GH or GH-releasing peptide (GHRP)-6 modulates the brain IGF system. Treatment of adult male rats with GHRP-6 or GH for 1 wk significantly increased IGF-I mRNA levels in the hypothalamus, cerebellum, and hippocampus, with no effect in cerebral cortex. Expression of the IGF receptor and IGF-binding protein (IGFBP)-2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
0
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 74 publications
7
89
0
1
Order By: Relevance
“…Treatment with GHRP-6 did not increase GFAP levels but stimulated proliferation in the hypothalamus and hippocampus. GHRP-6 and ghrelin stimulate the proliferation of a wide number of cells including osteoblasts (Kim et al 2005), cardiomyocytes (Pettersson et al 2002), somatotrophs (Dieguez & Casanueva 2000), endothelial cells (Rossi et al 2009) and adipocytes (Thompson et al 2004) and may also affect the CNS by protecting neurons from apoptosis (Frago et al 2002, 2011, Delgado-Rubin de Célix et al 2006, Delgado-Rubin et al 2009). We also evaluated the possible effect of GH and GHRP-6 on neuron number and did not observed any changes in the levels of Tuj1 in the hypothalamus or hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Treatment with GHRP-6 did not increase GFAP levels but stimulated proliferation in the hypothalamus and hippocampus. GHRP-6 and ghrelin stimulate the proliferation of a wide number of cells including osteoblasts (Kim et al 2005), cardiomyocytes (Pettersson et al 2002), somatotrophs (Dieguez & Casanueva 2000), endothelial cells (Rossi et al 2009) and adipocytes (Thompson et al 2004) and may also affect the CNS by protecting neurons from apoptosis (Frago et al 2002, 2011, Delgado-Rubin de Célix et al 2006, Delgado-Rubin et al 2009). We also evaluated the possible effect of GH and GHRP-6 on neuron number and did not observed any changes in the levels of Tuj1 in the hypothalamus or hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that GH, one of the main regulators of growth and metabolism (Conway-Campbell et al 2007, Lichanska & Waters 2008, also has profound effects in the CNS (Harvey et al 1993, Nyberg 2000, Donahue et al 2006, being involved in the regulation of emotion (Burman & Deijen 1998), cognitive functions, memory (Deijen et al 2011), appetite (Stoving et al 1999) and neuroprotection (Scheepens et al 1999, Frago et al 2002, Lyuh et al 2007. Indeed, the GH receptor (GHR) is expressed in diverse areas throughout the CNS (Fraser et al 1990, Le Greves et al 2005 where this hormone has been shown to be involved in numerous cellular activities such as stimulation of mitosis, cell proliferation and differentiation (Frago et al 2002, Ajo et al 2003.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations